Creation of the Enterprise Bankruptcy Prevention System in Lithuania - Purlys, Česlovas (Ekonomika, 2001)
The article deals with Enterprise Insolvency and Bankruptcy problems mainly defaults of acting legislation as well as monitoring of bankruptcy procedures. The analysis of the situation in bankruptcy process is provided and the main reasons are described. The article shows that to solve the problems described to design the enterprise rehabilitation system is needed. In suggestions for designing and implementing the system one of the effective ways is restructuring of the enterprises. According to the author of the article restructuring is understood as frame of measures such as re-engineering of the enterprise, setting up new technologies, innovations and reorganization of management and work, renovation of facilities, restructuring of enterprises’ debts, etc. The structure of the system is provided and suggestions for implementation are described. The principle ideas of the new Enterprise bankruptcy law and Enterprise restructuring law that have been put by the author into Enterprise restructuring law and the article are provided. The Laws are described as the main parts of mechanism for strengthening competitiveness of enterprises’ and whole Lithuanian industry. The important measures for solving the enterprises’ bankruptcy and restructuring problems: setting up new institutions, Enterprise restructuring center, Enterprise restructuring foundation as well as reorganization of courts and training of judges for enterprise restructuring cases are suggested. The Governmental acts for implementation of the laws and methodology of restructuring of enterprises should be prepared immediately. The administrators for enterprise restructuring must be trained up to the implementation of the Enterprise restructuring law begins and bankruptcy administrators should be retrained. The quality vocational training of judges and administrators as well as social workers dealing with the bankruptcy and restructuring procedures are suggested